3 Aerobic exercise protects against heart failure in mice. (March 2019) - Lu, L; Zhuang, HW; Zhang, YL
Abstract : Objective: Studying the relationship between aerobic exercise and HRV is conducive to improving cardiovascular health and reducing the incidence of heart disease by aerobic exercise. Methods: 34 8-week-old male mice with well-functioning hearts were selected by sonography. The mice were divided into three groups: 8 in group A, 13 in group B and 13 in group C. Group A was a control group, and mice in groups B and C were subjected to severe aortic coarctation. After surgery, mice in group B returned to normal life and those in group C exercised 30 min/day for 12 weeks. Results: Compared with group A, the mice in group B experienced an increase in left ventricular end-systolic diameter at 6 weeks, a decrease in the left ventricular ejection fraction and the short axis shortening rate, hypertrophy of the heart and left ventricular enlargement. Compared with group B, the mice in group C experienced a decrease in left ventricular end diastolic diameter and left ventricular end systolic inner diameter and an increase in left ventricular ejection fraction and the short axis shortening rate. However, the above values did not reach the criteria of group A. Conclusion: Continuous aerobic exercise can play a role in protecting the hearts of mice with heart failure.